Impact of Global Warming on South Asia Low Pressure and Regional Cloud Cover: Impact of GW on South Asian Low Press & Cloud Cover. - Baig, Mirza Jawwad; Iqbal, M Jawed; Riaz, Syed Muhammad Fahad; Iqbal, Syed Tanveer (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Clouds perform a very unique function in whole of the atmospherics. They respond differently to the same scenario. Analyzing more than second half of the last century synoptic climatic data, it is observed that climatic parameters are sensitive to the increasing temperature. In North Atlantic cloud cover increases with temperature while it works the other way in South Asia. By using the Center of Action (COA) technique, it is suggested that the intensity of South Asia Low pressure (spread over from north India to Saudi Arabia) has been increasing from mid 70s. It is also found that the declining trend in regional cloud cover has some links with weakening low pressure system.